An insight into the distribution of pygmy grasshoppers (ORTHOPTERA: TETRIGIDAE) in the Klang Valley, Malaysia - Norfatihah Aisyah Abd Rahim,; Amira Aqilah Muhammad,; Nurul Ashikin Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The ecology of pygmy grasshoppers in Southeast Asia is generally understudied, especially in rapidly developing areas in Malaysia. This study aims to record the species assemblage and investigate the habitat preferences of pygmy grasshoppers in selected locations across the Klang Valley, Malaysia. Overall results recorded 16 Tetrigidae species from three subfamilies (Metrodorinae, Tetriginae and Scelimininae) and two tribes (Criotettigini and Thoradontini). Among these, nine species exhibited a preference for forest environments, while three species demonstrated an affinity for urban habitats. Four species can adapt to both habitat types, signifying their greater tolerance towards environmental pressure. Unweighted Pair Group Method with Arithmetic Mean (UPGMA) dendrogram based on Jaccard similarity coefficient showed distinct clusters between urban and forested habitats in terms of the species composition, supported by the result of the nonmetric multidimensional scaling (NMDS) analysis. Systolederus cinereus and Bolivaritettix sp. are widely distributed as it can be found at most of the studied locations. It is also found that species presence is highly influenced by the habitats’ environmental conditions as 13 out of 16 species were present in the forested habitats. Based on these findings, pygmy grasshoppers have the potential to become bioindicators for the environment, owing to their sensitivity to habitat conditions.